Numerical investigation of V shaped three elements resonator for optical closed loop system - Iraj Sadegh Amiri; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2019)
This study have outlined numerical investigation of V shaped three element resonator. The stability parameter is measured against back mirror curvature radius, back mirror phase angle, focusing length, focusing mirror phase angle, folding range in both S plane and T plane. The stability parameter is changed in positive and negative trend under the operating system parameters. The stability parameter should be optimized in order to achieve high performance efficiency of resonator system. Beam radius variations are also measured versus focusing range, folding range, and back mirror phase angle. It is clear that the negative effects of increasing system parameters on beam radius variation in both S plane and T plane.